2020
DOI: 10.1097/md.0000000000018837
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between intestinal mucosal lesions and hepatic dysfunction in patients without chronic liver disease

Abstract: Patients with cirrhosis are known to develop small bowel mucosal lesions. However, the occurrence of mucosal lesions in patients with abnormal liver function test results in the absence of chronic liver disease has not been fully evaluated. This study aims to examine the association between small bowel endoscopic lesions and liver dysfunction in patients without confirmed chronic liver disease. Two hundred ninety six consecutive patients who met the selection criteria underwent capsule endoscopy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this study, rats in the model group showed significant liver injury after long-term administration of ethanol. Levels of serum LDH, AST, and NOS significantly increased (Baghdasaryan et al 2019;Sehgal et al 2020;Wu et al 2020;Zou et al 2020), suggesting abnormal liver function and liver cell injury. MDA levels in liver tissue increased significantly and those of GSH decreased, suggesting lipid peroxidation damage in liver tissue.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, rats in the model group showed significant liver injury after long-term administration of ethanol. Levels of serum LDH, AST, and NOS significantly increased (Baghdasaryan et al 2019;Sehgal et al 2020;Wu et al 2020;Zou et al 2020), suggesting abnormal liver function and liver cell injury. MDA levels in liver tissue increased significantly and those of GSH decreased, suggesting lipid peroxidation damage in liver tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Among the former, telangiectasias, angiodysplastic-like lesions, varices, and active bleeding can be detected, while the latter may include ulcers, edema, strictures, and mucosal erosions [18 , 19] .…”
Section: Discussionmentioning
confidence: 99%